Urothelial bladder carcinoma with major clinical presentation as overactive bladder, without hematuria: case report and literature review - M., Alexander de J. Rafaelano; Navarro, Junior J. Araiza; Sosa, María Isabel Tolentino; Reyes, Fernando López; Gutiérrez, Marlene de la Peña (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The urothelial carcinoma is the most common type of bladder cancer, comprising approximately 90% of cases in the United States. The most common symptom of bladder cancer is macroscopic hematuria, increased urinary frequency, urgency, or irritative symptoms may occur. Generally, occurs in elderly people, about 9 out of 10 people are over 55 years old, with the average age at diagnosis of 73 years. Males are more likely than women to have this neoplasm with a probability of 1 in 27 (for women the probability is 1 in 89). Most bladder cancers begin in the inner layer, also called the urothelium or transitional epithelium. As it advances, it invades the layers of the bladder and can invade adjacent structures, often metastasizing to distant lymph nodes, bones, lungs or the liver. Among the cancers that originate in the bladder authors have: Urothelial carcinoma (transitional cell carcinoma), squamous cell carcinoma, adenocarcinoma, small cell carcinoma, sarcoma. Hematuria occurs in the majority of patients with urothelial carcinoma. Symptoms such as dysuria, frequency, urgency and pain may also occur, or it may also be asymptomatic. In this case report, an atypical presentation of bladder cancer is shown, simulating the symptomatology of a Hyperactive Bladder Syndrome.